EVALUATION OF ANTIFUNGAL ACTIVITY OF PHYTOCHEMICALS SCREENED FROM OREGANUM VULGARE AGAINST VULVO-VAGINAL CANDIDIASIS USING MOLECULAR DOCKING METHODOLOGY - Manisha Tripathy , Aparajita Mohapatra , Prabhasinee Sahoo , Soumya Jal (International Journal of Modern Agriculture, 2020)
A vertiginous demand of herbal medication, compared to that of synthetic drugs has gained popularity in the developed as well as developing nations. The increasing significance of plants as supplement for chemically formulated drugs, is due to their natural origin, which helps combatting the side effects that are generally associated with medications. The Ethnic world and the tribes in Indian continent are bestowed with a deeper knowledge when it comes to recognizing medicinal plants and their utility in curing various diseases. Phytochemicals are plant based; non-nutritive compounds that are gaining recognition due to enormous health benefits associated with them. In the present study, Origanum vulgare plant was screened for its phytochemicals, in order to understand its benefits in the cure of candidiasis. Candidiasis is an infection caused by a group of fungi from the genus Candida. One of the pivotal enzymes associated with the occurrence of Candidiasis is dihydrofolate reductase. Here, molecular docking technique was used to screen the phytochemicals that could efficiently act with the enzyme. The study was carried out using BIOVIA Discovery Studio. The strength of the interaction between the phytochemicals from Origanum vulgare, was evaluated against the enzyme based on the values of -CDocker energy and -CDocker interaction energy. Higher values skewed towards the positive side for both the parameters implies that certain phytochemicals such as, apigenin, linalool, luteolin, caryophyllene, germacrene, sabinene, ocimene, sputhalenol have potentials to deactivate the enzyme dihydrofolate reductase and interrupts the life cycle of Candida.